Temporal and bathymetric distribution of juveniles and adults of the speckled swimming crab Arenaeus cribrarius from coastal waters of southern Brazil - Ribeiro Da Silva, Alexandre [UNESP]; Barioto, João Gabriel [UNESP]; Grabowski, Raphael Cezar [UNESP]; Castilho, Antonio Leão [UNESP] (Springer Nature, 2017)
This study evaluated the temporal and bathymetric distribution of the speckled swimming crab Arenaeus cribrarius from coastal waters of southern Brazil. Monthly samples were taken at five distinct depths throughout one year in the adjacent area from Babitonga Bay, Southern Brazil. Data on environmental conditions (temperature, salinity, granulometry and organic matter) were collected and their association was tested using Multiple Linear Regression and Principal Component Analysis. Juveniles and adults showed different distribution patterns according to depth, with juveniles being more abundant in the shallower areas. The increase in temperature favors the juvenile distribution, while the distribution of adults was related to finer sediments. The pattern of distribution observed for adults might be associated with burrowing habits, or with the search for colder (and consequently deeper) waters, which are richer in nutrients. The high abundance of juveniles in shallower areas might be influenced by the Coastal Water mass that provides higher water temperatures in the summer, and by the Babitonga Bay estuarine complex, which can be an important source of organic matter. We conclude that this region represents a nursery ground for the studied species and is essential to preserve Babitonga Bay in order to maintain A. cribrarius in this region, since this area has suffered from anthropic impacts.
Keywords: Brachyura; nursery; Portunidae; zonation